BENTUK PERMAINAN YANG MEMOTIVASI ANAK LEPAS DARI ORANG TUA/PENGASUH DI KELOMPOK BERMAIN - Melati Indri Hapsari; Heri Martono (Direktorat Pembinaan Guru dan Tenaga Kependidikan Pendidikan Anak Usia Dini Kementerian Pendidikan dan Kebudayaan bekerjasama dengan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2009)
Teacher’s creativity in identifying and determining kinds of games appropriate to meet their children’s needs is required to enable him/her to motivate them to be free from their parents or nurses. How to get the children free from their parents or nurses and to get them into the activitives in the playgroup become a problem for the teacher. This research assumed that this problem could be solved by selecting approprate games for the children. The purposes of this research were to identify the kinds of games and discover the appropriate ones to keep the children free from their parents. Exploring the facts in three play groups (Tunas Bangsa, BBC Kid’s Center, and Anak Cerdas) in Semarang, the research discovered a number of games and the appropriate ones to motivate the children to join the activities in the play group. Based on the analysis, the research gave the teachers some recommendations in using the selected games.